Intuitive Understanding of Parabolas

Want to understand parabolas without having to read a textbook? This post demystifies parabolas by describing their most important features. Knowing these points will make any discussion on these graphs easier to follow.

Functions of the form $$y = ax^2 + bx + c$$ are known as a quadratic functions. Graphs of quadratic functions are known as parabolas.

Roughly speaking, a parabola resembles an elongated bowl. Three questions can be asked.

  1. Where is the ”bottom” of this bowl?
  2. Is the bowl right side up or upside down?
  3. How wide is the bowl?

It turns out that knowing the answers to there three questions gives everything you need to know about a parabola.

Let’s start with the quadratic function $$ y = x^2 $$ This is plotted below.

Graph of \( y = x^2 \). Vertex is \((0,0)\).

The ”bottom” of this parabola (called the vertex) is indicated by the red dot in the above graph, which is \((0,0)\).

Let’s say I want to change this parabola. First, I can move it. How? Let’s say I want to move the “bottom” of the parabola from \((0,0)\) to \((2,1)\). It turns out that if $$ y = (x \, – s)^2 + t $$ then the resulting parabola will look like the previous one, but the vertex (the “bottom”) will be \((s, t)\).

Since I want to move the vertex from \((0,0)\) to \((2,1)\), I should set \(s = 2\) and \(t = 1\) in the above formula to get \( y = (x \, – 2)^2 + 1\).

I get the following parabola as a result.

Graph of \( y = (x \, – 2)^2 + 1 \). Vertex is \((2,1)\).

Let’s say I want to “flip” the “bowl” by “flipping” the graph of \( y = (x \, – 2)^2 + 1 \). It turns out that the graph of $$ y = -(x \, – s)^2 + t $$ is the same as the graph of $$ y = (x \, – s)^2 + t $$ except that the “bowl” is “flipped”.

The graph of \( y = -(x \, – 2)^2 + 1\) is as follows. Note that the vertex of the parabola does not change.

Graph of \( y = -(x \, – 2)^2 + 1 \). Vertex is \((2,1)\).

The above graph is a graph of the equation \( y = -(x \, – 2)^2 + 1 \). This can be written as \( y = a(x \, – 2)^2 + 1 \) with \( a = -1 \)

Let’s say I changed \( a \) to the negative number \( -10 \). Because \( -10 < -1 \), the resulting graph will be narrower than before. Specifically, the graph of \( y = -10(x \, – 2)^2 + 1\) is as follows. Note that the vertex does not change.

Graph of \( y = -10(x \, – 2)^2 + 1 \). Vertex is \((2,1)\).

Comments

No comments yet. Why don’t you start the discussion?

    Leave a Reply

    Your email address will not be published. Required fields are marked *